RNAvigator: A Pipeline to Identify Candidates for Functional RNA Structure Elements - Delli Ponti, Riccardo; Wang, Jiaxu; Wan, Yue; Huber, Roland G. (Frontiers in Virology, 2022)
Identifying structural elements on long and complex RNAs, such as lncRNAs and RNA viruses, can shed light to the functionality and the mechanisms of such RNAs. Here we present RNAvigator, a tool able to identify elements of structural importance by using experimental SHAPE data or SHAPE-like predictions in conjunction with stability and entropy assessments. RNAvigator recognises regions that are the most stable, unambiguous, and structured on RNA molecules, and thus potentially functional. When relying on predictions, RNAvigator uses the CROSS algorithm, a neural-network trained on experimental data that achieved an AUC 0.74 on HCV SHAPE-MaP data, and which was able to improve the predictive power of Superfold. By using RNAvigator, we are able to identify known functional regions on the complete HCV genome, including the regulatory regions CRE and IRES, and the 3’ UTR of DENV-1, a region known for the presence of structural elements essential for its replication. We envision that RNAvigator will be a useful tool to study long and complex RNA molecules by using known chemical probing data or, if they are not available, by employing predicted profiles.